The pharaoh key - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J. Gideon Crew novel., 2018)
When his former employer goes missing, Gideon Crew, reeling from his terminal diagnosis, pursues the long-awaited translation of the Phaistos Disc, an ancient tablet that could end or save his life.